Association Between Vestibular Migraine and Migraine Headache: Yet to Explore. Issue 3 (March 2020) - Abouzari, Mehdi; Goshtasbi, Khodayar; Moshtaghi, Omid; Tan, Donald; Lin, Harrison W.; Djalilian, Hamid R.
Abstract : Objectives: To evaluate if patients with a diagnosis of vestibular migraine (VM) by the International Classification of Headache Disorders (ICHD) criteria have meaningful differences in symptomatology and disease characteristics when compared to patients with concurrent vestibular symptoms and migraine that do not meet ICHD criteria. Methods: Patients who presented for the evaluation of vertigo were provided a detailed questionnaire about dizziness and migraine symptoms. Patients were assigned to either VM cohort (met ICHD criteria for VM) or migraine headache (MH) cohort (met ICHD criteria for migraine with or without aura but not VM). Disease characteristics, symptomatology, quality of life, and perceived stress score were compared between the cohorts. Results: The VM cohort demonstrated a shorter duration of vertigo episodes, 11 ± 22 hours versus 84 ± 146 hours in the MH cohort. In the VM cohort, 81% reported experiencing migraine headaches during episodes of vertigo, versus 61% in the MH cohort. All patients in the VM cohort reported a previous diagnosis of migraine headache, whereas 9% of the MH cohort had not been previously diagnosed by another physician. There was no difference in quality of life or perceived stress scores between the cohorts. Conclusions: A large proportion of vertigo patients with migrainous features do not meet the ICHD criteria for VM. The differences between cohorts represent selection bias rather than meaningful features unique to the cohorts. As such, VM and MH with vestibular symptoms may exist on a spectrum of the same disease process and may warrant the same treatment protocols. Abstract : Supplemental Digital Content is available in the text